STRATEGI GURU DALAM MENGEMBANGKAN KEMAMPUAN NUMBER SENSE: STUDI KUALITATIF DI KELAS I SDN RAWAMANGUN 09 JAKARTA - Afifah Ambaryanti; Chrisnaji Banindra Yudha; Prayuningtyas Angger Wardhani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze teacher strategies in developing first-grade students' number comprehension skills at SDN Rawamangun 09 Jakarta. This study used a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation studies with first-grade teachers, the vice principal, and students. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, and was strengthened through triangulation of sources and techniques to ensure data credibility. The results of the study indicate that teachers implemented three complementary strategies in developing students' number comprehension skills, namely (1) the use of concrete teaching aids (manipulatives) through the Concrete-Representational-Abstract (CRA) approach, (2) number discussions realized through the provision of scaffolding, and (3) play-based learning (learning while playing). The research findings indicate that the use of concrete teaching aids is the most prominent strategy in learning practices because it is in accordance with the concrete operational cognitive development stage of first-grade students. These three strategies begin with strategic planning that considers student abilities, is adapted to the diversity of student abilities, and is supported by collaboration between teachers and parents. This study also identified several inhibiting factors, including heterogeneity in student abilities, limited time, and concentration. This research implies that developing number understanding in early elementary school students requires the integration of concrete, experiential learning, dialogic interactions through scaffolding, and the support of a learning ecosystem that continuously engages the school.